Electrical Engineering Rancang Bangun Alat Proteksi Arus Diferensial Pada Transformator 3 Phase Berbasis Arduino: Sistem Proteksi - Meisy Zahira; Arif Gunawan; Muzni Sahar (Politeknik Caltex Riau, 2021)
The transformer is one of the important equipment in the electrical system. If there is a disturbance in the transformer, it can cause damage to the transformer and also to the distribution of electric power. So that the transformer requires the main protection in the form of differential current protection. In this study the design of a differential current protection device on an Arduino-based three-phase transformer. To meet these needs, this differential current protection device uses Arduino Mega 2560 as a data processor and controller. The measurement uses the ACS712 20A current sensor and the ZMPT101B voltage sensor. The workings of this design refer to the tripping characteristics of ANSI 87T and the slope refers to the characteristics of the T60 relay. Based on the results of the tests carried out, the protection device does not disconnect the transformer with the load.This is because the load imbalance disturbance in one phase does not cause a differential current in the transformer winding. Besides, this design is equipped with a keypad for inputting the multiplier factor of the CT ratio and the real time value of the protection device. The value of the differential current and transformer voltage will be displayed on the LCD display and the current data on this protection will be stored on a micro SD card so that it can make it easier to monitor the condition of the transformer used.